2008
DOI: 10.1590/s0074-02762008000600009
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile associated with chronic and acute human schistosomiasis mansoni

Abstract: The production and regulation of interleukin (IL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
1
27
0
3
Order By: Relevance
“…De Morais performed one research which showed that after SWAP stimulation, chronic patients, particularly hepatointestinals, produced higher levels of IL-4 in comparison with acute patients, suggesting the presence of a type 2 cytokine profile in these patients. Following SEA and SWAP stimulation, HS patients showed increased levels of IFN-gamma when compared with acute patients, indicating that HS disease in humans was also associated with a type 1 cytokine response (de Morais et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…De Morais performed one research which showed that after SWAP stimulation, chronic patients, particularly hepatointestinals, produced higher levels of IL-4 in comparison with acute patients, suggesting the presence of a type 2 cytokine profile in these patients. Following SEA and SWAP stimulation, HS patients showed increased levels of IFN-gamma when compared with acute patients, indicating that HS disease in humans was also associated with a type 1 cytokine response (de Morais et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Cellular immune responses, although involved in resistance, mediate most of schistosome-related pathology [203, 204], which can be divided into acute and chronic diseases based on disease progression. Acute schistosomiasis is a debilitating febrile disease which often occurs in individuals with no experience of infection.…”
Section: Immune Responses During Schistosome Infectionmentioning
confidence: 99%
“…High IFN-γ levels in controls have been reported before in response to AWA and SEA. 16 It is possible that components of these antigenic mixtures bear pathogen-associated molecular patterns and react with pattern recognition receptors on immune cells, such as monocytes, B-lymphocytes , or natural killer (NK) cells. The IFN-γ response to AWA in uninfected subjects might be produced by NK cells, which can readily release IFN-γ in response to stimulation by pathogen-associated molecular patterns (PAMPs).…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that it makes biological sense for IL-13, IL-5, and IFN-γ to have a central role in the response to infection with Schistosoma spp. 16,30 Because of IL-13's function in signaling B cells to switch to IgE production and IL5's and IL-13's principal role in recruiting and activating eosinophils, these cytokines are important in the initial response to invading cercaria and later on, to schistosomula. 30 Eosinophilia is known to be associated with Katayama syndrome, 17,19 and the stronger IL-5 and IL-13 responses that we found may reflect stronger activation of eosinophils at the time of infection in the travelers with Katayama syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation